Penegakan Hukum Terhadap Tindak Pidana Pencurian Sepeda Motor di Semarang (Studi di Pengadilan Negeri Semarang) - Enan Andarwati (Publikasi Indonesia, 2023)
Whether by physical force or the threat of such force, stealing is always an act of coercion that involves the taking of another person's property or rights. There are factual and subjective components to theft. As a result, the author dubs his/her work